Effect of dietary fish oil intake on ubiquitin ligase expression during muscle atrophy induced by sciatic nerve denervation in mice. (27th May 2019) - Komiya, Yusuke; Kobayashi, Chiaki; Uchida, Naoyasu; Otsu, Shohei; Tanio, Tatsuki; Yokoyama, Issei; Nagasao, Jun; Arihara, Keizo
Abstract: Dietary fish oil intake improves muscle atrophy in several atrophy models however the effect on denervation‐induced muscle atrophy is not clear. Thus, the aim of this study was to investigate the effects of dietary fish oil intake on muscle atrophy and the expression of muscle atrophy markers induced by sciatic nerve denervation in mice. We performed histological and quantitative mRNA expression analysis of muscle atrophy markers in mice fed with fish oil with sciatic nerve denervation. Histological analysis indicated that dietary fish oil intake slightly prevented the decrease of muscle fiber diameter induced by denervation treatment. In addition, dietary fish oil intake suppressed the MuRF1 (tripartite motif‐containing 63) expression up‐regulated by denervation treatment, and this was due to decreased tumor necrosis factor‐alpha (TNF‐α) production in skeletal muscle. We concluded that dietary fish oil intake suppressed MuRF1 expression by decreasing TNF‐α production during muscle atrophy induced by sciatic nerve denervation in mice.